USE OF SOCIAL NETWORK IN MARKETING IN HANOI, VIETNAM A SMALL CASE STUDY - V, Do N; M; 4 Other students, Dao T (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
This Term project will give you an overview of using social networks in marketing – which is a very popular approach to selling products and services nowadays. The Term Project contents 4 Parts. Part 1 provides the definition of social network and its popularity in daily life in general and in marketing in particular. Followed by part 1, part 2 of the term project clarifies the differences between traditional marketing and social network marketing and then transitions from the traditional approach to this modern one. Given the transition, part 3 explains the reasons why marketers prefer social network marketing and at the same time points out some disadvantages that marketers normally face with. Finally, the term project ends with the most outstanding case study – Facebook, illustrating how the social network is being used in marketing.